Status of insecticide resistance on Aedes aegypti (L.) and Aedes albopictus (Skuse) in Kampar, Perak, Malaysia - Dinesh Rajendran; Farrah Najwa Adnan; Aslinda Ummi Awang Besar; Mahani Yusoff; Wan Fatma Zuharah (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The threat of dengue and Chikungunya transmitted by Aedes mosquitoes continues to cause concern to the public resulting to control by the usage of insecticides. However, the heavy dependence on such chemicals has caused the development of resistance towards insecticides. The objective of this study is to determine the insecticide resistance status of Aedes aegypti and Aedes albopictus in Kampar, Perak, Malaysia. Ovitraps were placed in the urban and suburban region of Kampar, Perak and collected after seven days. Identified Ae. aegypti and Ae. albopictus females aged from three to five days were exposed to two different chemical classes, pyrethroids (0.75% permethrin & 0.05% deltamethrin) and organophosphates (5% malathion & 0.25% pirimiphos-methyl) using WHO adult bioassay test. For Ae. aegypti the knockdown time recorded for 0.75% permethrin was significantly longer at KT50 of 222.475 minutes and KT95 of 1742.297 minutes as compared to 0.05% deltamethrin and 5% malathion (F=82.19, df=4, P<0.05). Meanwhile the knockdown time for Ae. albopictus recorded for 5% malathion was significantly longer at KT50 56.827 minutes of and KT95 105.175 minutes as compared to 0.75% permethrin and 0.05% deltamethrin (F=968.82, df=4, P<0.05). No knockdown was recorded for 0.25% pirimiphos-methyl for both species. Aedes aegypti was confirmed to be resistant to 0.75% permethrin, 0.05% deltamethrin and 0.25% pirimiphos-methyl tested after 24 hours, while Ae. albopictus was confirmed resistant towards 0.25% pirimiphos-methyl (4 ± 0.20% mortality) and 5% malathion (77 ± 3.85%) and possibly resistant to 0.05% deltamethrin (93 ± 4.65% mortality). No mortality was found in the control group. This study concludes that the constant usage of insecticides in Kampar especially in the urban area has caused the development of resistance in Ae. aegypti and Ae. albopictus.